Políticas públicas e agricultura camponesa: análise do PAA e do PNPB nos municípios de Ipameri e Jataí-GO - Peixoto, Ângela Maria Martins (2016)
The focus of this research are the public policies of rural development of the first decade of the 21th century in the scope of a territorial approach through a theoretical and empirical investigation of two programs directed to the peasant agriculture: the Food Acquisition Program (known as Programa de Aquisição de Alimentos – PAA) and National Program of Production and Biodiesel Use (known as Programa Nacional de Produção e Uso do Biodiesel - PNPB). The goal is to understand the effects of the PAA and PNPB for the peasant agriculture, mostly in the micro regions of Catalão and Sudoeste de Goiás to verify the logic related to the implementation of the programs beyond their formal guidelines, i.e., how political decisions of territory management in the federal level influence local and regional levels. Thus, the methodological procedures consisted in bibliographical review about the theme; data collecting of secondary source among some institutions and agencies as the Brazilian Institute of Geography ans Statistics (IBGE), Ministry of the Agrarian Development (MDA); Supply National Company (Conab), National Agency of Oil, Natural Gas and Biofuels (ANP), among other ones; and data collecting of primary source through field research on the selected microrregions. A priori we detach the importance of these programs for the productive insertion of the peasants, composing a political agenda, considering the historically exclusionary type of elaborated policies for the agriculture and that privileged only the great rural producers. However, we must investigate the effectivity of the territorial approach to legitimize the peasant autonomy through the contraposition of the institutional bias and its implementation. PAA has given different territorial effects than the ones of PNPB. The first characterizes as an economic and social policy, and although has not discussed in the debate about food sovereignity, has advanced to decrease food and nutritional insecurity and in the formation of institutional markets for the commercialization of food from the peasant production. The second has been a way of subordination of the peasant agriculture to the agricultural and industrial capital, once the whole productive process is managed by the great industries of biodiesel, which are the majors benefited by the social strategy of the program through the Social Fuel Seal (Selo Combustível Social), beyond setting itself as incentive to soy monoculture, main raw material used in the program. The consequences of the operationalization of these programs has shown two elementary questions of the current dynamics of Brazilian agriculture: the production of food versus the production of energy, as result of the intentions of the elaboration process of such public policies. From these elements, we analyze the (i)materials conditions of existence of peasant agriculture and its remaining in the rural space.